2015
DOI: 10.1164/rccm.201501-0126oc
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Recipient Age and Diagnosis on Health-related Quality-of-Life Benefit of Lung Transplantation

Abstract: Lung transplantation confers large HRQL benefits, which vary by recipient diagnosis, but do not differ substantially in older recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 43 publications
3
83
0
1
Order By: Relevance
“…Comparison to other patients showed that the CF patients experienced fewer problems with mobility and sleep. This finding is in line with the results of previous studies regarding the influence of baseline diagnosis on HRQoL after transplantation 39, 40, 41, 42. Due to a lifetime of lung disease before LTx, the CF patients could not experience the “full” health that other groups of patients could have enjoyed in earlier stages of life.…”
Section: Discussionsupporting
confidence: 91%
“…Comparison to other patients showed that the CF patients experienced fewer problems with mobility and sleep. This finding is in line with the results of previous studies regarding the influence of baseline diagnosis on HRQoL after transplantation 39, 40, 41, 42. Due to a lifetime of lung disease before LTx, the CF patients could not experience the “full” health that other groups of patients could have enjoyed in earlier stages of life.…”
Section: Discussionsupporting
confidence: 91%
“…(23) While subjects in both that cohort and ours experienced similar improvements in SF12-PCS defined HRQL, we observed substantially smaller improvements in EQ5D and EQVAS in absolute terms. Further, we observed that older patients had significantly less improvement in SF12 whereas the effect of increasing age on HRQL in the Canada cohort was negligible.…”
Section: Discussionsupporting
confidence: 54%
“…(922) Nonetheless, relatively few studies focused on HRQL itself as a primary outcome in lung transplantation have been published since the LAS overhaul. (23) Thus, given the clinical primacy of HRQL, there is a need for contemporary information on the effect of lung transplantation on general and respiratory-specific HRQL…”
Section: Introductionmentioning
confidence: 99%
“…Second, our analysis focuses on the survival benefit of transplantation; it does not address other important outcomes such as quality of life (QOL), improvements in which have been demonstrated in previous analyses of lung transplantation (42)(43)(44)(45)(46)(47)(48). Other end points including composite end points of survival, QOL, and cost could change our interpretation of the relative benefit of transplantation.…”
Section: Limitationsmentioning
confidence: 99%